Industrializable Synthesis of Fmoc-Ala-Thr-OH Pseudodipeptide as a Key Intermediate of Peptide Drugs - Li, Xi-An; Yue, Li-rong; Xu, Jiao; Liang, Xiao-feng; Zhou, Meng-jiao; Hu, Dong-yan; Ren, Hua-zhong; Feng, Jia-fu; Han, Guang-tian (Synthesis, 2025)
A new process for industrially synthesizing Fmoc-Ala-Thr-OH pseudodipeptide, which is a key intermediate for the synthesis of peptide drugs, is presented in four steps in overall 46% yield from Fmoc-L-Ala-OH. The process did not use column chromatography, and the characteristic of dipeptide salting with some organic base was cleverly utilized for purification. The suitable organic base for forming salt with the dipeptide was found after screening, and finally the synthesis was completed by recrystallization. The whole synthesis process is beneficial to industrial production and cost control. The purity of the product was over 99%.
Keywords: synthesis; pseudodipeptide; drugs; recrystallization; industrial